Cohesion beyond EU territoriality? Reflections from the ESPON project TERCO - James Scott; Sárolta Németh; Matti Fritsch; Heikki Eskelinen (European Regional Science Association (ERSA), 2012)
Territorial co-operation has become an integral part of European Union Cohesion Policy, and is regarded as an instrument towards achieving the EU policy objective of Territorial Cohesion. Since the inception of the INTERREG Community Initiative in the early 1990s, EU-funded cross-border, transnational and inter-regional co-operation has enabled diverse actors to co-operate in a variety of fields, thus contributing to territorial integration through the common identification of problems and solutions for territorial development, exchange of knowledge, benchmarking, processes of learning and, not the least, 'getting to know each other'. Also across its external borders, the European Union has facilitated cross-border co-operation through a (though, uneasy) combination of INTERREG and TACIS funding, which has recently been replaced and simplified by the European Neighbourhood and Partnership Instrument (ENPI). Cross-border co-operation across the external border both shares similarities and exhibits differences with co-operation across the EU's internal borders. Although, the types of actors involved and priorities and project contents on the ground are generally similar, high politics and large economic trends have significant impact on EU-external border regions. This is true also for the Finnish-Russian borderlands, which had been for a long time separated by a closed border and the distress of forced land cession, and which, two decades after the collapse of the Soviet Union, includes an EU-external 'neighbourhood'. Co-operation across this external border is also conditioned by the macro-level framework of factors such as political relations between the EU and Russia, intricate and variable customs regulations, changing border regimes and a general 'ambiguity between co-operation and control' (Cronberg 2003). Leaving from the assumption that territorial cooperation contributes to territorial cohesion/integration across borders, we seek answers to questions including the following: To what extent this is true in the context of external borders of the European Union? Are there any signs of territorial cohesion/integration across the Finnish-Russian border? Using findings from the empirical analysis carried out in the TERCO project (ESPON 2013), this paper thus also sheds light on the potential schisms between internally oriented cohesion policy and externally oriented neighbourhood policy.
Keywords: R58; 330; territorial co-operation; EU Cohesion Policy; Cross-border co-operation; EU external borders